Aromaterapi Lavender dalam Menurunkan Tingkat Nyeri dan Kecemasan Pasien dengan Anestesi Spinal - Prayitno Prayitno; M. Hafiduddin (Jurnal Kabar Masyarakat, 2023)
Pain and anxiety are common complaints experienced by patients after spinal anesthesia. One non-pharmacological method that can be used to reduce pain and anxiety is lavender aromatherapy. This study aimed to determine the effectiveness of lavender aromatherapy in reducing pain and anxiety levels in patients undergoing spinal anesthesia. This study used a quasi-experimental design with a pre-test and post-test approach in a single group without a control group. A total of 50 patients undergoing spinal anesthesia received lavender aromatherapy through a diffuser for 15-30 minutes before and after the anesthesia procedure. Pain levels were measured using the Visual Analog Scale (VAS), and anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS). The results showed a significant reduction in patients' pain and anxiety levels after the administration of lavender aromatherapy (p < 0.05). Therefore, lavender aromatherapy is proven to be effective as a non-pharmacological method to help reduce pain and anxiety in patients undergoing spinal anesthesia.